2015
DOI: 10.18388/abp.2014_880
|View full text |Cite
|
Sign up to set email alerts
|

Methyl jasmonate, yeast extract and sucrose stimulate phenolic acids accumulation in Eryngium planum L. shoot cultures

Abstract: Eryngium planum L. has been reported as a medicinal plant used in traditional medicine in Europe. The tissue cultures may be an alternative source of the biomass rich in desired bioactive compounds. The purpose of this study was to investigate the influence of the biotechnological techniques on the selected phenolic acids accumulation in the agitated shoot cultures of E. planum. Qualitative and quantitative analyses of those compounds in 50% aqueous - methanolic extracts from the biomass were conducted by appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…In shoots cultured on the solid MS medium, the content of rosmarinic acid was 3.5-times higher and of caffeic acid it was 24.33-times higher than in basal leaves of the intact plant (Kikowska et al 2012). The analyses of E. planum shoots agitated in the liquid MS media confirmed the presence of rosmarinic, chlorogenic, and caffeic acids in all the examined materials, but the content significantly increased after elicitation (Kikowska et al 2015). The content of two phenolic acids-rosmarinic acid and chlorogenic, was measured in shoots and roots of E. maritimum.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…In shoots cultured on the solid MS medium, the content of rosmarinic acid was 3.5-times higher and of caffeic acid it was 24.33-times higher than in basal leaves of the intact plant (Kikowska et al 2012). The analyses of E. planum shoots agitated in the liquid MS media confirmed the presence of rosmarinic, chlorogenic, and caffeic acids in all the examined materials, but the content significantly increased after elicitation (Kikowska et al 2015). The content of two phenolic acids-rosmarinic acid and chlorogenic, was measured in shoots and roots of E. maritimum.…”
Section: Resultsmentioning
confidence: 74%
“…Although there are approximately 230-250 species of Eryngium in the world, only few have been introduced into in vitro cultures, namely E. foetidum (Arockisamy and Ignacimuthu 1998;Ignacimuthu et al 1999;Arockisamy et al 2002;Martin 2004;Chandrika et al 2011), E. planum (Kikowska et al 2012(Kikowska et al , 2015Thiem et al 2013), E. maritimum (Kikowska et al 2014), E. campestre (Kikowska et al 2016), and E. viviparum (Ayuso et al 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research aimed at developing productive micropropagation systems with cytogenetic evaluation of in vitro regenerated plants, and stabilizing cell (callus, cell suspension cultures) and organ (shoots, roots) cultures of three Eryngium species. Moreover, the potential of the systems for production of the selected secondary metabolites and the assessment of selected biological activities were tested (Thiem at al., 2010;Thiem et al, 2011;Kikowska et al, 2012;Thiem et al, 2013;Kikowska et al, 2014a,b;Kikowska et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, addition of Jasmonic acid or methyl jasmonate to Mentha piperita suspension cultures resulted in high accumulation of phenolic compounds (Krzyzanowska et al 2012). Recently, Kikowska et al (2015) reported the optimum condition of elicitation for cultivation of shoots of Eryngium planum in liquid MS media in the presence of 100 μM MeJA for 48 h. This resulted in an approximately 4.5-fold increase in rosmarinic, chlorogenic and caffeic acid in plant material compared with the control. The results in the present study revealed that addition of jasmonic acid caused an increase in caffeic acid and total sugar content of the cultures used.…”
Section: Discussionmentioning
confidence: 99%